2017
DOI: 10.1155/2017/9853108
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Level Disturbs the Resveratrol-Evoked Curtailment of CX3CL1/CX3CR1 Signaling in Human Placental Circulation

Abstract: Hyperglycemia-induced hyperactivity of chemokine CX3CL1 (fractalkine) occurs in the human placenta. Anti-inflammatory/antioxidant activities of resveratrol (3,5,4′-trihydroxy-trans-stilbene) are related to the modulation of chemokine CX3CL1 and its receptor, CX3CR1, signaling pathways. We examined the influence of high glucose (25 mmol/L glucose; HG group; N = 36) on resveratrol-mediated effects on CX3CL1 and TNF-α production by the placental lobule, CX3CR1 expression and contents of CX3CR1, TNF-α receptor 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The corresponding genes are shown in Figure 12B . CCL2 ( 35 ) and CX3CL1 ( 36 ) are essential cytokines in the TNF signalling pathway. CXCL9 ( 37 ) and CX3CL1 ( 38 ) can inhibit the chemokine signalling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding genes are shown in Figure 12B . CCL2 ( 35 ) and CX3CL1 ( 36 ) are essential cytokines in the TNF signalling pathway. CXCL9 ( 37 ) and CX3CL1 ( 38 ) can inhibit the chemokine signalling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that decreased fetal growth may be associated with the worsening of FPG within the respective normal reference range. Alternatively, other studies also demonstrated that hyperglycemia induced upregulation of the C-X3-C motif chemokine ligand 1 (CX3CL1)/C-X3-C motif chemokine receptor 1 (CX3CR1) signaling pathway, which is known to disturb placental perfusion ( 30 , 31 ). This notion is supported by a study by Stridsklev et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since CX3CL1 levels in the blood are linked to indicators of insulin resistance in people with GDM, researchers investigated whether resveratrol therapy might reduce CX3CL1/CX3CR1 production. Interestingly, in light of their results, the authors reported the therapeutic effects of resveratrol on reducing hyperglycemia and reductions in CX3CL1 production ( Szukiewicz et al, 2017 ). Thus, pregnant women with metabolic disorders and euglycemia should benefit most from resveratrol’s anti-inflammatory effects on placental CX3CL1/CX3CR1 signaling.…”
Section: Therapeutic Strategies To Target CXC Chemokines In Pe and Gdmmentioning
confidence: 99%